METHICILLIN-RESISTANT STAPHYLOCOCCI PREVALENCE IN CANCER PATIENTS AT A TERTIARY CARE CANCER CENTRE – A RETROSPECTIVE STUDY - MURUGESAN, SARAVANAN; TK, SUJINA; SAMUEL, SAJANI; KE, SARATH; RUDRAPATHY, PARTHIBAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of this study was to investigate the prevalence of Methicillin-resistant Staphylococcus aureus (MRSA) and MR-coagulase-negative staphylococci (CoNS), as well as their antimicrobial resistance, in various samples from cancer patients in North Kerala. Methods: The retrospective study was conducted at a tertiary care cancer centre in North Kerala over a 4-year period from January 2016 to December 2019. During the study, data on all cultures from cancer patients was analyzed. This study was approved by Institutional Review Board (IRB). Non-duplicate isolates of staphylococci were included in the study obtained from various clinical specimens. Species identification and antimicrobial susceptibility testing was done using automated methods. Results: During the period of 4 years (2016–2019), a total of 1176 isolates of staphylococci were analyzed, out of which 784 were S. aureus isolates (68%) and 392 (32%) isolates were CoNS. Among CoNS species, Staphylococcus epidermidis and Staphylococcus haemolyticus were the most common species of CoNS, representing 39% and 28% of the total CoNS identified. Overall prevalence of methicillin resistance in S. aureus and CoNS was found to be 50.7% and 55.6%, respectively. Methicillin-resistant staphylococci isolates showed higher resistance to multiple drugs than methicillin-sensitive staphylococci isolates. Conclusion: This study demonstrates that MRS could also be a haul in cancer patients at North Kerala. A higher percentage of MR-CoNS isolates are multidrug resistant than MRSA isolates. Glycopeptides and linezolid still stay the mainstay for treatment for MRS infections.